Analisis Yuridis tentang Rancangan Undang-Undang Perlindungan Pekerja Rumah Tangga dari Perspektif Keadilan dan Kemanfaatan Hukum: Studi terhadap Rancangan Undang-Undang Perlindungan Pekerja Rumah Tangga - Nakita, Alaika Ziva; Tjoneng, Arman (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The Constitution of the Republic of Indonesia guarantees protection for all Indonesian citizens, particularly in ensuring the right to obtain employment and receive fair wages. Article 27 paragraph (2) of the 1945 Constitution of the Republic of Indonesia provides the fundamental principle that every person has the right to work and to earn a livelihood that is decent for humanity. However, in reality, many violations still occur, especially against domestic workers (PRT). Based on the author’s findings, many domestic workers continue to experience unfair treatment such as discrimination, physical and sexual violence, as well as inadequate wages. This reality becomes the responsibility of the state to provide protection for domestic workers. Therefore, the Government of the Republic of Indonesia, together with the House of Representatives, has initiated discussions on the Draft Law concerning the Protection of Domestic Workers. In this research, the author analyzes the Draft Law on the Protection of Domestic Workers from the perspective of the values of justice and legal utility. The method used in this research is descriptive analysis, which describes and illustrates the realities that occur in society and connects them with the prevailing laws and regulations. This study also applies a normative juridical approach, which uses legislation and legal literature as the main sources of data. The results of this study indicate that Indonesian society, especially domestic workers, urgently needs a legal framework as a form of protection and legal certainty to guarantee their safety and welfare. Therefore, the enactment of the Law on the Protection of Domestic Workers must be prioritized.